Study on Photo Degradation of Dyes from Aqueous Solutions of their Binary Mixture, using TiO 2 as the Oxidant with Different Sources of Energy - Shanthi, S.; Priya, K. Sathya (New Innovations in Chemistry and Biochemistry Vol. 1, 2021)
Photodegradation has been widely employed in water and waste water treatment Of all the methods like froth flotation coagulation etc., photodegradation appears to offer the best prospects for overall treatment of dyestuff effulent. Solar photo catalytic oxidation technique using semiconductors like TiO2, ZnO etc has a land mark in the field of waste water treatment especially for the removal of organics and dye stuffs. Of the various semiconductors, TiO2 is a promising material. Utilisation of solar energy makes the process green and economically viable. In places where we don’t have enough solar radiation we are in need of other sources of energy.In the present study,photodegradation of aniline blue and crystal violet dyes from aqueous solutions of their binary mixture was carried out using TiO2 as photocatalyst. By carrying out photodegradation, under different experimental conditions, the optimum values of experimental parameters required for maximum degradation was found out. The studies were conducted utilising a variety of energy sources, including solar and microwave radiation. The rate constant and activation parameters were calculated using degradation studies conducted at temperatures of 250°C, 350°C, and 450°C. In every way except duration and dose of photo catalyst, both energy sources cause deterioration in the same way. Microwave radiation takes less time than solar radiation, however microwave radiation requires a higher dose of photo catalyst. These findings will aid in the design of industrial effluent treatment plants.